Sejarah Dan Perkembangan Pemenuhan Standar Pendidikan Sekolah Dasar Fatma Kenanga Kota Bengkulu - Reza (Manajer Pendididikan, 2024)
The aims of this research are: 1) Knowing the philosophical, juridical, historical, and empirical considerations of the establishment of the Fatma Kenanga Elementary School in Bengkulu City; 2) Knowing the dynamics of the development of the Fatma Elementary School in Bengkulu City, seen from 8 national education standards. The research method used in this research is qualitative research with descriptive data. This research will use a historical research method which is relative and this research uses cross-sectional research. This study in general concludes that Fatma Kenanga Elementary School was established based on the deed of establishment of the Fatma Al Islami Foundation Number 36 notary Irwan, SH on 19 August 2014, and the school's operational permit was obtained on 10 June 2017. Then the development of 8 national education standards in schools has not been fully implemented due to the condition of the school that is still developing and the limited location of the school which is still small.